Pengaruh Motivasi dan Lingkungan Kerja terhadap Kinerja Pegawai pada Kantor Camat Sibolga Sambas Kota Sibolga - Sahru Razak Sukriadi Tanjung; Mansur Tanjung; Kaharuddin Kaharuddin (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of motivation and work environment on employee performance at the Sibolga Sambas Subdistrict Office, Sibolga City. The research method used is a quantitative approach with an associative research type. Data collection techniques include questionnaires, interviews, and documentation. Data analysis was conducted using validity and reliability tests, multiple linear regression, t-test, F-test, and coefficient of determination with the help of SPSS software. The results show that partially, motivation and work environment have a positive and significant effect on employee performance. Simultaneously, both variables also have a significant effect on employee performance with a contribution of 66.5%, while the remaining is influenced by other factors outside this study. Therefore, improving motivation and creating a conducive work environment can enhance employee performance